Kesesuaian Penyelenggaraan Pelayanan Kefarmasian di Puskesmas - Andi Leny Susyanty; Yuyun Yuniar; Max J. Herman; Nita Prihartini (Media Penelitian dan Pengembangan Kesehatan, 2020)
Abstract Pharmaceutical services have been gradually applied in primary health services both in terms of pharmaceutical management and clinical pharmacy services. In order to support the implementation, the standard has been amended several times, resulting Permenkes Number 74 of 2016 Concerning the Pharmaceutical Services Standard in Public Health Centre (puskesmas) as the most updated one. This study aimed to determine the suitability of the implementation of pharmaceutical service standards in the management of medicine and clinical pharmacy at the puskesmas. The cross-sectional research design was conducted in February-November 2017. The selection of provincial locations was carried out purposively. Data collection tools were questionnaires and a list of standard pharmacy services at the puskesmas. Data were analyzed descriptively. The results showed that 54.5% of the puskesmas did not have pharmacists as the responsible person and only 18.2% of the puskesmas had sufficient pharmacist and pharmaceutical technical staff for both drug management activities and clinical pharmacy services. Comprehensive drug management activities in accordance with pharmaceutical service standards at the puskesmas have been implemented in 96.7% of puskesmas with pharmacists. Comprehensive clinical pharmacy service activities according to pharmacy service standards at puskesmas are only applied in 23.3% of puskesmas with pharmacists. The availability and ability of pharmacists in providing clinical pharmacy services in puskesmas need to be a concern. Abstrak Pelayanan kefarmasian secara bertahap telah mulai diterapkan di pelayanan kesehatan dasar, baik dalam kewajiban pengelolaan farmasi maupun pelayanan farmasi klinis. Untuk mendukung hal tersebut, standar pelayanan kefarmasian di puskesmas telah beberapa kali mengalami perubahan dan terakhir diperbaharui dengan Permenkes Nomor 74 Tahun 2016 Tentang Standar Pelayanan Kefarmasian di puskesmas. Studi ini bertujuan mengetahui kesesuaian pelaksanaan standar pelayanan kefarmasian dalam pengelolaan obat dan farmasi klinik di puskesmas. Desain penelitian potong lintang dilakukan pada bulan Februari-November 2017. Pemilihan lokasi provinsi dilakukan secara purposif. Alat pengumpul data berupa kuesioner dan daftar tilik standar pelayanan kefarmasian di puskesmas. Analisis data dilakukan secara deskriptif. Hasil studi menunjukkan bahwa sebanyak 54,5% puskesmas belum mempunyai tenaga apoteker sebagai penanggung jawabnya dan hanya 18,2% puskesmas yang jumlah apoteker dan tenaga teknis kefarmasiannya mencukupi untuk kegiatan pengelolaan obat dan pelayanan farmasi klinik. Kegiatan pengelolaan obat yang komprehensif sesuai dengan standar pelayanan kefarmasian di puskesmas sudah diterapkan di 96,7% puskesmas yang memiliki apoteker. Kegiatan pelayanan farmasi klinis yang komprehensif sesuai standar pelayanan kefarmasian di puskesmas hanya diterapkan di 23,3% puskesmas yang memiliki apoteker. Ketersediaan dan kemampuan apoteker dalam memberikan pelayanan farmasi klinik di puskesmas perlu menjadi perhatian.